Imagens e estereótipos do Brasil nos livros didáticos franceses - Ulhôa, Leonardo Moreira (2013)
French textbooks, in particular the Geography ones, are teaching resources that guide teaching practices and substantially contribute to the understanding of the organization of geographical space from the view of different landscapes in the world. The images in this context are the primary documents of iconography. This work analyzes them from the stereotypes that are conveyed about the Brazilian reality. The research approaches a discussion on the epistemological notion of image which is linked to the reality as an external referent. From this viewpoint we discuss whether the pictures represent a true reflection of the Brazilian reality as they can be understood both as presence and substitution of something that is distant from the reader. In other words we have evaluated the limits of the image as a mediator between the real world and what can be read by the students who use it. Therefore, we do not intended to create a hierarchical dualism between true images and false images, but to understand them from the personal intentions of the authors who, in partnership with publishers, define the choice of illustrations and individualized ways of seeing, showing and hiding the world. We have questioned their adaptations and/or inadequacies regarding the Brazilian reality. For that, we use the method of phenomenology to analyze the images of Brazil in France textbooks, published from 1996 to 2011. In parallel we have developed a framework that allows us to describe and then examine the elements considered most relevant in the construction of each image of Brazil. Such procedures showed evidence that the teaching themes that address the Brazilian reality, associated with the subjectivity of the textbooks authors, reverberate in their iconographic positioning. This means that the choice of image format, associated with geographic content requires a strategy to guide the different meanings over Brazil in French textbooks. Thus, we have drawn the main frameworks applied in the iconography of textbooks of that country for presentation and/or enactment of the Brazilian territory. We have found that the image, however, is not spontaneously obtained; it should be understood as an elaboration of reality; it is not reality itself. We finally understand that the way a considerable part of the Brazilian images is portrayed, represented, and repeated at least since the 1990s, seems to contribute, solidify and nurture a unilateral idea about knowledge of Brazil. This refers to an advocated image model that often fits in a context of negativity and generalized conceptions about reality. It is not inappropriate to think that these images show particularized evidence of the Brazilian reality and should be considered as stereotypes.